On ideal supra topological space - Taha H. Jasim; Reem H. zaben (Tikrit Journal of Pure Science)
In this paper we introduces via of ideal supra topological space classes of concepts (I-supra -dense, ∗-supra dense, ∗-closed supra, ∗-perfect supra) in ideal supra topological space. At last we study and investigate some characterization of these concept for there more we introduces some continuous mapping, and there properties